Age and Sex Differences in Acute and Osteoarthritis-Like Pain Responses in Rats. (14th August 2019) - Ro, Jin Y; Zhang, Youping; Tricou, Christina; Yang, Dan; da Silva, Joyce T; Zhang, Ruixin
Abstract: In this study, we investigated age and sex differences in acute and chronic pain in rats. Groups of young (3–6 months) and aged (20–24 months) male and female Fischer 344 rats were used to assess basal thermal and mechanical thresholds, capsaicin-induced acute nocifensive responses and c-Fos expression in the spinal cord, and monoiodoacetate (MIA)-induced knee osteoarthritis (OA)-like pain responses. There was a significant sex, but not age, effect on thermal threshold on the hindpaw and mechanical threshold on the knee joint. No significant age and sex differences in capsaicin-induced nocifensive and c-Fos responses were observed. MIA induced a greater peak reduction of weight-bearing responses in aged males than young rats. Aged females developed the most profound weight-bearing deficit. With knee joint sensitivity as a primary outcome measure, MIA induced more pronounced and longer-lasting hyperalgesia in older rats, with aged female rats showing the worst effect. These data suggest that age may not have significant effect on acute nociceptive processing, but it significantly impacts OA-like pain, making aged rats, especially females, more vulnerable to chronic pain conditions. These preclinical models should provide important tools to investigate basic mechanisms underlying the impact of age and sex in chronic pain conditions.